A simple and effective approach for evaluating unconfined hydrogen/air cloud explosions. (24th May 2018) - Pu, Liang; Shao, Xiangyu; Li, Qiang; Li, Yanzhong
Abstract: The topic of hydrogen safety assessment has been focused by many researchers. The overpressure evaluation of vapor cloud explosion (VCE), is an important issue for both designing and evaluating on chemical plants, as well as buildings. Unknown flame radius history limits the original acoustic approximation model's application. The objective of this work is to develop an achievable model for hydrogen/air deflagration assessment in engineering applications, and the model should have high computational efficiency. A tentative scheme that starts from flame/piston speed history solving was adopted, and the flame/piston radius and acceleration history will be obtained subsequently. Thus, the overpressure history for far field could be gotten based on the acoustic approximation model. A simplified scheme was employed for the region inside the flame cloud. The model proposed in this paper could be solved in several seconds, because there are no differential equations but only algebraic equations. The model was verified by hydrogen/air deflagration tests from small scale to large scale. Compared with the experimental data, the model appeared well agreements in the medium and large scale cases. In the small scale cases, the model obtained acceptable solutions. Highlights: An achievable acoustic approximation model was developed. Overpressure history of the region inside the flammable cloud was considered. The model has good accuracy in medium and large scale deflagration cases. The model has high computational efficiency compared with CFD model.